ETHNIC AND CULTURAL INTERACTION IN NORTH SUMATRA: A HISTORICAL STUDY OF BATAK, MALAY, AND CHINESE INTERACTION IN MEDAN - Marpaung, Luthfy Hamid Hussen Yuzmar; Paralihan, Hotmatua (International Journal of Cultural and Social Science, 2025)
North Sumatra is a province with high ethnic and cultural diversity, making it a dynamic yet challenging social space. Medan City, as the provincial capital, is a hub for interaction among Batak, Malay, and Chinese communities. This study examines the dynamics of these interethnic relations in the context of history, urbanization, and contemporary multiculturalism. Using a qualitative approach with historical and sociocultural methods, data were collected through literature review, in-depth interviews with community leaders and academics, and participatory observation. The findings reveal that interethnic relations in Medan are shaped by colonial legacies, social inequality, prejudice, and limited intercultural dialogue. Although cultural initiatives such as festivals foster symbolic interaction, they have not resolved structural issues of segregation. Strengthening social integration requires inclusive public policies, intercultural education, and urban planning that promotes equal encounters. This study contributes to understanding multicultural dynamics in urban Indonesia and offers insights for fostering social harmony in diverse societies.